2021
DOI: 10.1111/pai.13461
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of ATM gene mutations in Iranian patients with ataxia‐telangiectasia

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
(115 reference statements)
1
6
0
Order By: Relevance
“…One of the limitations of our study is that we did not have extra access to the material to check the level of ATM protein as well as its activity in our patients. Our previous report also showed that approximately 90% of AT patients with classical presentations had a homozygous mutation (84); however, we found that more than 60% of the reported variant AT patients had a compound heterozygous mutation. However, we did not find a significant genotype-phenotype association with regards to neurological groups in the study overall, indicating an additional influence of shared environmental factors or disease-modifying genes.…”
Section: Discussionsupporting
confidence: 41%
“…One of the limitations of our study is that we did not have extra access to the material to check the level of ATM protein as well as its activity in our patients. Our previous report also showed that approximately 90% of AT patients with classical presentations had a homozygous mutation (84); however, we found that more than 60% of the reported variant AT patients had a compound heterozygous mutation. However, we did not find a significant genotype-phenotype association with regards to neurological groups in the study overall, indicating an additional influence of shared environmental factors or disease-modifying genes.…”
Section: Discussionsupporting
confidence: 41%
“…The c.67C>T variant was present in three unrelated patients among which two had homozygous and one had heterozygous variants (Five allelic variants). The germline variant at this position has also been associated with mantle cell lymphoma 37 , gastric cancer 38 and A-T 39 (ClinVar Accession: VCV000232248.14; Invitae: SCV000748724.5). The c.8473C>T variant was also found in two unrelated A-T cases.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with truncating variants in this study had severe disease with an early onset 44 . A large report from Iran reported 9 novel variants out of 43 mutations in forty-three A-T cases 4 . Fievet et al reported 49 ATM variants in 36 patients with typical and atypical A-T along with functional characterization of variants 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the virtual issue on "Inborn Errors of Immunity" aims at providing the readers of PAI a collection of topical reviews on some of the major immunological pathways that can be affected by pathological genetic variants causing IEIs and a selection of original articles highlighting clinical observations from cohort studies of well-known conditions, as well as original discoveries that extend the genetic and clinical features of less commonly observed IEIs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In their review of IEIs caused by defects in the DNA damage response pathways, Fournier and Colleagues 3 Additional reviews of the areas of IEIs characterized by defects of actin cytoskeletal dynamics, the JAK-STAT pathways, and type I interferon disorders have been commissioned and will be available in the near future. These works will complement the current collection and provide the readers of PAI with additional timely updates and perspectives on the scientific and clinical aspects of some of the major disease subgroups in the field of IEIs.…”
mentioning
confidence: 99%